Modelo de atenção e acesso ao diagnóstico e tratamento da tuberculose na Rede Básica de Saúde de um município da Bahia, Brasil, 2011 - Maia, Ana Margarete Cordeiro da Silva (2012)
Study on the model of health care and access to diagnosis and treatment of Tuberculosis (TB) in the network of Primary Care (PC) in a city of Bahia, Brazil in 2011. It was set as goal to analyze the model of Health Care in the TB Control Program (TCP) of Feira de Santana-BA, considering the flow of work, practices of the team and the problem solving demanded by patients with TB, to discuss the dimensions of analysis of users' access to services for TB Control in the city. The methodology: qualitative study, in a critical and reflective perspective, which allowed working with the involvement and participation of individuals through different perspectives, knowledge and practices to enable reflection on the concrete reality of a particular social context. It was used as technique of data collection: semi-structured interviews and systematic observation. The study subjects were 21 people, distributed among two groups of representation: group I (health workers - 02 doctors, 05 nurses, one nursing technician and 04 Community Health Agents (CHA), group II (users – 09 registered at Tuberculosis Reference unit). Data analysis was guided by three stages - sorting, grading and final analysis - by the technique of thematic content analysis and analytic flowchart. By the produced data two categories emerged: Category 1 - Model of Care in the Program for Tuberculosis Control: doctor-centered and (dis) articulated in the basic health network of a city of Bahia, Brazil, Category 2 - The dimensions of access to the Tuberculosis Control Program in a city Bahia, Brazil. The results show that the model of health care in the TCP of the studied city is guided by three models namely: the practices of the team in the TCP where the care model has been developed within a logic centered on the production of procedures and in nuclei professionals in a disjointed way, in particular doctor-centered way; in the flow of work most users has sought the public and private hospitals, private clinics and Reference Unit (RU) followed by PC to identify the diagnosis of TB, however, the treatment has only been accomplished by Reference Unit; and solvability, the access to some procedures have been hampered denoting the fragility of PC to ensure the solvability of the problems demanded by users. However, workers and users are satisfied with the services provided by the RU, where attention is concentrated. About the dimensions of access, it was established five dimensions of analysis: 1) Geographical Access to the TCP, 2) Organization of care to enable users’ access to the TCP, 3) Access driven by medical care, 4) Access to TB treatment and 5) Prejudice hindering access to the TCP. Thus, the mode of transportation is a factor that facilitates or impedes access to health services, and the predominant displacement is by foot. The study shows that workers had difficulty in making home visits, because of the availability of transport. Regarding the form of organization of TB the procedures are centralized in RU and medical care, however, both users and professionals are satisfied with the adequate supply of medicines, and show benefits, particularly in the RU for the TCP. It is concluded that the prejudice that surrounds the TB has hampered the access, once patients prefer to be accompanied at RU to not be labeled as a person with TB, which is a hinder factor for the diagnosis and treatment of the disease.